2007
DOI: 10.1128/ec.00104-07
|View full text |Cite
|
Sign up to set email alerts
|

A Rho3 Homolog Is Essential for Appressorium Development and Pathogenicity of Magnaporthe grisea

Abstract: The small GTPase Rho3 is conserved in fungi and plays a key role in the control of cell polarity and exocytosis in yeast. In this report, we show that a Rho3 homolog, MgRho3, is dispensable for polarized hyphal growth in the rice blast fungus Magnaporthe grisea. However, MgRho3 is required for plant infection. Appressoria formed by the Mgrho3 deletion mutants are morphologically abnormal and defective in plant penetration. Conidia of the Mgrho3 deletion mutants are narrower than those of the wild-type strain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…p190 GAP is inhibited by phosphorylation and activated by PP2A-mediated dephosphorylation (Mori et al 2009). Similar results have been recently shown for Rho GAP activation in a number of different eukaryotic cells (Sopko et al 2007;Zheng et al 2007;Toure et al 2008;McAvoy et al 2009;Mori et al 2009;Wolfe et al 2009). Since rga5D and rga1D null mutants suppress lethality of Etd1-depleted cells, inhibition of Rho1 by PP2A-Pab1 could be exerted through dephosphorylation and activation of these Rho1 GAPs (see model in Figure 8).…”
Section: Rho1 Inhibition By Pp2a-pab1supporting
confidence: 75%
“…p190 GAP is inhibited by phosphorylation and activated by PP2A-mediated dephosphorylation (Mori et al 2009). Similar results have been recently shown for Rho GAP activation in a number of different eukaryotic cells (Sopko et al 2007;Zheng et al 2007;Toure et al 2008;McAvoy et al 2009;Mori et al 2009;Wolfe et al 2009). Since rga5D and rga1D null mutants suppress lethality of Etd1-depleted cells, inhibition of Rho1 by PP2A-Pab1 could be exerted through dephosphorylation and activation of these Rho1 GAPs (see model in Figure 8).…”
Section: Rho1 Inhibition By Pp2a-pab1supporting
confidence: 75%
“…The clakel2 mutant formed abnormal appressoria on glass slides; however, mutant hyphal growth on potato dextrose agar medium and conidiation, though with a reduced amount of spores, was similar to that of the wild type (18). In M. oryzae, Zheng et al (28) have shown that Magnaporthe grisea Rho3 (MgRho3) is dispensable for vegetative hyphal growth but not for plant infection, as the appressoria formed by the ⌬Mgrho3 strain are morphologically abnormal and defective in plant penetration. However, it is important to note that unlike in Magnaporthe, the deletion of TEAC in A. nidulans leads to significantly reduced vegetative growth (10) and a likely decrease in conidiation.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Rho family of small GTP-binding proteins act as pivotal signaling switches and play a key role in morphogenesis during pathogenic development in M. oryzae (28,29). In Aspergillus nidulans, cell end marker proteins TeaA (Tea1), TeaR (Mod5), KipA (Tea2), and TeaC (Tea4) have been shown to be important for polarized hyphal growth (10,24).…”
mentioning
confidence: 99%
“…Dünkler and Wendland (2007) found that the Rho3 was required for the polarized growth and cell separation in Candida albicans. Zheng et al (2007) reported the Rho3 was dispensable for polarized hyphae growth, but required for the appressorium development and virulence in Magnaporthe oryzae.…”
Section: Introductionmentioning
confidence: 99%